2013
DOI: 10.1177/0022219413500991
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement Among Juvenile Detainees

Abstract: The literature has long pointed to heightened frequencies of learning disabilities (LD) within the population of law offenders; however, a systematic appraisal of these observations, careful estimation of these frequencies, and investigation of their correlates and causes have been lacking. Here we present data collected from all youth (1,337 unique admissions, mean age 14.81, 20.3% females) placed in detention in Connecticut (January 1, 2010–July 1, 2011). All youth completed a computerized educational screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
10
0
5
Order By: Relevance
“…In a subsequent study, the screener was computerized and administered to a sample of 1,337 youth (mean grade = 9.04) detained in Connecticut (Grigorenko et al, 2015). A subsample ( n = 410) of these youth received the Wide Range Achievement Test , in addition to the educational screener.…”
Section: Learning Difficulties Learning Disabilities and Delinquencmentioning
confidence: 99%
“…In a subsequent study, the screener was computerized and administered to a sample of 1,337 youth (mean grade = 9.04) detained in Connecticut (Grigorenko et al, 2015). A subsample ( n = 410) of these youth received the Wide Range Achievement Test , in addition to the educational screener.…”
Section: Learning Difficulties Learning Disabilities and Delinquencmentioning
confidence: 99%
“…Adolescent delinquents’ reading ability lags their peers by an average of 2 years; evidence to this effect has been around for decades (Brunner, 1993; Critchley, 1968; Finn, Stott, & Zarichny, 1988; Margolin, Roman, & Harari, 1955; Mulligan, 1969). More contemporary studies consistently show that mean reading age peaks at 12 years for juvenile offenders (Alm & Andersson, 1995; Grigorenko et al, 2015; Snowling, Adams, Bowyer-Crane, & Tobin, 2000; Wheldall & Watkins, 2004), and depending on the delinquent population, up to half may experience reading and literacy deficits (McMackin, Tansi, & Hartwell, 2005; Vacca, 2008). In one large-scale study, Grigorenko and colleagues (2015) found that almost 25% of all youth detained in Connecticut in 1 calendar year displayed learning deficiencies, 4 times the rate in the general population.…”
Section: Language Development and Communication Concernsmentioning
confidence: 98%
“…More contemporary studies consistently show that mean reading age peaks at 12 years for juvenile offenders (Alm & Andersson, 1995; Grigorenko et al, 2015; Snowling, Adams, Bowyer-Crane, & Tobin, 2000; Wheldall & Watkins, 2004), and depending on the delinquent population, up to half may experience reading and literacy deficits (McMackin, Tansi, & Hartwell, 2005; Vacca, 2008). In one large-scale study, Grigorenko and colleagues (2015) found that almost 25% of all youth detained in Connecticut in 1 calendar year displayed learning deficiencies, 4 times the rate in the general population. By second grade, almost half of all students who will later become delinquents have experienced reading delays (Meltzer, Levine, Karniski, Palfrey, & Clarke, 1984), and by adulthood, more than 60% of inmates have no better than a sixth-grade reading level (Alm & Andersson, 1995; Vacca, 2004).…”
Section: Language Development and Communication Concernsmentioning
confidence: 98%
“…Youth who become involved in the JJ system are more likely than their peers to face additional challenges. For example, between a quarter and a third have identified special learning needs as defined by federal law (Grigorenko et al, 2015).…”
Section: From School To Prison and Backmentioning
confidence: 99%